Pakaian dan Identitas Keagamaan: Makna dan Motif Penggunaan Cadar bagi Mahasiswi Perguruan Tinggi Agama Islam di Kalimantan Tengah - Zulkarnain, Ali Iskandar; Ajahari, Ajahari; Khalfiah, Yuliani; Saudah, Saudah (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2022)
The purpose of this study is to explore the meaning and motives of using the veil by students of an Islamic university in Central Kalimantan. This study is qualitative research with a phenomenological approach. Data collection was carried out from January to October 2020 with 33 informants from 5 Islamic Religious Universities in Central Kalimantan. Data were collected through in-depth interviews, participant observation, and documentary studies. The data obtained were then analyzed using the qualitative analysis of the Miles and Huberman model, namely data exposure, data reduction, and concluding. Departing from the analysis of the data obtained, it can be concluded that the meaning and motives of PTAI students in Central Kalimantan in using the veil do not stand alone on theological grounds, but also have a relationship with the socio-cultural dimensions that are part of the dynamics of the student's life.Keywords :